2016
DOI: 10.1080/01639625.2016.1246034
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem in Adult Prison Population: The Development and Validation of the Self-Esteem Measure for Prisoners (SEM-P)

Abstract: The main aim of the current study was to develop and validate the Self-Esteem Measure for Prisoners (SEM-P), composed of personal and prison self-esteem, among a systematically selected sample of prisoners (N = 1,794). Confirmatory factor analyses revealed that the SEM-P was best captured with the bifactor conceptualization reflecting two grouping factors (personal and prison self-esteem) and one general factor. Although factor loadings were stronger for the general factor, the two grouping factors evidenced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
(64 reference statements)
1
10
0
Order By: Relevance
“…The findings confirmed that SE functions as a twofold construct rather than as a monolithic form. This is in line with previous research of Debowska et al (2017), Hyland et al (2014), McKay et al (2014, and Boduszek et al (2012Boduszek et al ( , 2013. Secondly, it was to investigate a correlation between SE and spiritual factors.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…The findings confirmed that SE functions as a twofold construct rather than as a monolithic form. This is in line with previous research of Debowska et al (2017), Hyland et al (2014), McKay et al (2014, and Boduszek et al (2012Boduszek et al ( , 2013. Secondly, it was to investigate a correlation between SE and spiritual factors.…”
Section: Resultssupporting
confidence: 76%
“…According to Hyland et al (2014), people have different associations with positive and negative expressions. Debowska et al (2017) conclude that high SE associates with different psychological spans than its relative low SE.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations